Menotrophin Induced Autoimmune Hepatitis. (2nd September 2019) - Alqrinawi, Shurouq H.; Akbar, Nuralhuda; AlFaddag, Hind; Akbar, Shahrazad; Akbar, Lujayn; Butt, Sohail A.; Aljawad, Mohammed
Abstract : Menotrophin is a protein-based hormonal therapy. It is used as a fertility medication that is given as injection either subcutaneously or intramuscularly. Menotrophin has not been previously reported to cause drug-induced liver injury. Drug-induced liver injury (DILI) is commonly seen nowadays with the expansion of the drug industry. It is associated with prescribed medications, over the counter drugs, herbal and dietary supplements. We report the first case of Menotrophin-induced autoimmune hepatitis in a 26-year-old Caucasian woman who was diagnosed with primary infertility due to failure to conceive after five years of marriage. She had received several cycles of Menotrophin, then developed new onset jaundice and fatigue associated with increase in transaminases. She had normal baseline liver function and enzymes prior to receiving treatment with Menotrophin. Evaluation showed no evidence of viral hepatitis, metabolic, alcoholic or vascular causes of liver injury. Autoimmune screening was positive for antinuclear antibody (ANA) with titer of 1 : 640 fine speckled, immunoglobulin G (IgG) level was 1900 mg/dl. Antimitochondrial antibodies (AMA) and antismooth muscle antibodies were negative. Liver biopsy showed features of chronic hepatitis with interface hepatitis and prominence of plasma cells, which best reflects autoimmune hepatitis. Her liver enzymes and bilirubin completely normalized after discontinuation of further Menotrophin therapy and starting treatment with prednisolone and Azathioprine.